Pogranicze językowe jako element świata przedstawionego w literaturze polskiej XX i XXI wieku (na wybranych przykładach) - Sokólska, Urszula (Slavia Occidentalis, 2024)
The subject of consideration in this article are exemplary linguistic devices of borderland provenance, rather unknown to the general Polish, which clearly situate the place of action on the borderland of Polish-Belarusian-Lithuanian cultures and, consequently, represent an important element in building the atmosphere of Szczenięce lata by Melchior Wańkowicz and two novels by Krzysztof Gedroyć: Piwonia, niemowa, głosy and Piwonia odrodzona. Selected phenomena like narrowing (reduction) of e>i, y, akanye, pronunciation of nasals, confusion in the use of forms with e // Ø, mixing of consonants š , ž, č : s‘, z’, c’ : ś, ź, ć : s, z, c, the occurrence of the strengthening participle że in a reduced form, the use of the reflexive pronoun się next to an active verb, the disappearance of the onset n in prepositional phrases next to the personal pronouns he, she, it, the dominance in dependent cases - even in the unstressed position - of the longer form of personal pronouns, the construction for + D instead of C, the construction u mnie jest ‘I have’, expressions characteristic of borderland Polish, complex constructions and vocabulary. Attention has been drawn to the significant differences between the language of Wańkowicz the narrator, and the language of the characters in his novels, as well as to the lack of this difference between the language of the narrator and the language of the literary characters in Krzysztof Gedroyć’s novels Piwonia, niemowa, głosy and Piwonia odrodzona.In doing so, not only have the roots of both writers been identified, but also the authors’ extraordinary care to bring out the creative qualities of the dialect as an important component of the depicted world. As a result, the language of the cultural borderlands is revealed in the texts under discussion with full force and artistic intent.